2013
DOI: 10.1021/ja404697b
|View full text |Cite
|
Sign up to set email alerts
|

Across the Structural Re-Entrant Transition in BaFe2(PO4)2: Influence of the Two-Dimensional Ferromagnetism

Abstract: BaFe2(PO4)2 was recently prepared by hydrothermal synthesis and identified as the first two-dimensional (2D) Ising ferromagnetic oxide, in which honeycomb layers made up of edge-sharing FeO6 octahedra containing high-spin Fe(2+) ions (S = 2) are isolated by PO4 groups and Ba(2+) cations. BaFe2(PO4)2 has a trigonal R-3 structure at room temperature but adopts a triclinic P-1 structure below 140 K due to the Jahn-Teller (JT) instability arising from the (t2g)(4)(eg)(2) configuration. The triclinic crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The fact that the interplay between magnetic and lattice structures leads to reentrant phase transition is manifested in other compounds. For example, BaFe2(PO4)2 undergoes a rare reentrant structural transition owing to the competition between uniaxial magnetism and the Jahn-Teller distortion [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the interplay between magnetic and lattice structures leads to reentrant phase transition is manifested in other compounds. For example, BaFe2(PO4)2 undergoes a rare reentrant structural transition owing to the competition between uniaxial magnetism and the Jahn-Teller distortion [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Due to a substantial interlayer separation of the Fe layers separated by Ba 2+ and (PO 4 ) 3− insulating layers, BFPO is 2D electronically. BFPO was synthesized by Mentré and coworkers [22,23], who identified the rare 2D Ising FM nature with Curie temperature T C = 65 K. The very large calculated magnetocrystalline anisotropy is related to the large orbital moment. Our previous study [21] provided the relaxed atomic positions and revealed large exchange splitting ∆ ex =3 eV of the d 6 ion, enforcing the high spin S = 2 configuration with its filled and inactive majority d orbitals.…”
Section: A Structure and Symmetrymentioning
confidence: 99%
“…This separation length is such that this compound was identified as the unique "oxide" behaving as a genuine twodimensional Ising ferromagnetic phase with Tc = 65.5 K 19 . In addition, it shows a re-entrant rhombohedral ଵସ ሱۛۛሮ triclinic ሱۛሮ rhombohedral transition, driven by the competition between Jahn-Teller instability and stabilization of the system by the magnetic ordering 13 . At high temperature a reversible Fe-exsolution was recently demonstrated.…”
Section: Fe Exsolution In Bafe 2 (Po 4 ) 2 : State-of-the-art and Advmentioning
confidence: 99%